PENGARUH HUTAN BAKAU TERHADAP SEDIMENTASI - Besperi Besperi (Inersia: Jurnal Teknik Sipil, 2019)
The aim of this research is to contribute in engineering consideration especially to study the ability Rhizophora shrub to increase velocity of sedimentation. The research has done using phsycal modelling (prototype refer to Rhizophora aged 4 – 5 years old). Depht obtained by three time measuring with 10 minutes interval to obtain precision f measurement. Model has scale 1:10 base on facility.The result ofresearch shows that Rhizophora shrub can reduce velocity, the depth raise, and the velocity of sedimentation raise.